INTEGRATION OF TECHNOLOGY IN POSTER WRITING SKILL - Afrini Rahmi; Welsi Haslina; Ria Satini (Lembaga Penelitian dan Pengabdian Masyarakat STIES Babussalam, 2026)
The low interest of students in learning to write posters is the basis of the problem in this study. Therefore, an appropriate strategy is needed to increase student interest in writing posters. One of them is by using application-based learning media that does not require costs such as Microsoft Publisher. This study aims to describe the increase in interest in writing posters in junior high school students in Padang City using the Microsoft Publisher application. The method used in this study is collaborative Classroom Action Research (CAR). Data were collected using observation, questionnaires and interviews. The collected data were then analyzed to see the increase in student interest in learning to write posters using Microsoft Publisher learning media. The results of the study showed a significant increase in student interest in poster writing skills using Microsoft Publisher learning media. Additional features in Microsoft Publisher are an attraction for students to write posters. Students are helped to develop creative ideas with the help of features in Microsoft Publisher. Learning to write posters using Microsoft Publisher learning media can help students develop creative ideas in writing, especially posters.